PERILAKU SEKSUAL PRANIKAH PADA MAHASISWA KOST (STUDI KASUS PADA PERGURUAN TINGGI â€œXâ€ DI WILAYAH JAKARTA BARAT) - Yudia, Sharla Mega; Cahyo, Kusyogo; Kusumawati, Aditya (Fakultas Kesehatan Masyarakat, 2018)
One of the most complex teenage issues is free sex. College students pretained in a group of teen with age ranging from 18-24 years old. Because their campus is far from their home, most of them choose to stay in a boarding house. Lack of parental supervision and weak social control in the boarding house environment exacerbate sexual behaviour of college students. The purpose of this study is to describe premarital sexual behaviour of undergraduate student at University â€œXâ€ in West Jakarta Region. This type of research is qualitative research with in-depth interviews. Population studied are 6 informant who stayed at the boarding house and 8 triangulation informant which consist of 4 close friends and 4 girlfriends who stayed at boarding house. The results showed that the factors that caused college student to have a free sex is due to high amount of allowance that encourage them to try new things, the influence of the surrounding environment like friends, best friends or boyfriend or girlfriend, lack of attitude that doesnâ€™t care about the limit of friendship from the opposite sex, lack of supervision from the owner of the boarding house, believe in a stigma that rules were made to be broken, early sex education given from parents to their children is still very taboo, and an increasing accessible of media information.